2005
DOI: 10.4049/jimmunol.175.7.4528
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Two Active Sites of Human Complement Receptor Type 1 (CD35) in Complement Regulation: Implications for the Structure of the Classical Pathway C3 Convertase and Generation of More Potent Inhibitors

Abstract: The extracellular domain of the complement receptor type 1 (CR1; CD35) consists entirely of 30 complement control protein repeats (CCPs). CR1 has two distinct functional sites, site 1 (CCPs 1–3) and two copies of site 2 (CCPs 8–10 and CCPs 15–17). In this report we further define the structural requirements for decay-accelerating activity (DAA) for the classical pathway (CP) C3 and C5 convertases and, using these results, generate more potent decay accelerators. Previously, we demonstrated that both sites 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 54 publications
2
26
1
Order By: Relevance
“…Armed with this information on DAF, we then analyzed the extent of conservation of residues in DAF and in other C3 convertase regulators determined by mutagenesis to be important, either for cofactor activity or for DAA (12,18,21,22,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Whereas we found an absence of strict conservation of residues which distinguish the two functions, by focusing alignment on the sequence flanking the CCP2 and -3 junction where DAF function resides, we identified differences between those regulators that 1) mediate DAA and 2) mediate cofactor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Armed with this information on DAF, we then analyzed the extent of conservation of residues in DAF and in other C3 convertase regulators determined by mutagenesis to be important, either for cofactor activity or for DAA (12,18,21,22,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Whereas we found an absence of strict conservation of residues which distinguish the two functions, by focusing alignment on the sequence flanking the CCP2 and -3 junction where DAF function resides, we identified differences between those regulators that 1) mediate DAA and 2) mediate cofactor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our identification of a short peptide within this N-terminal domain may be helpful for future design of smaller peptidomimetic molecules that can replace the larger 3 SCRs in APT070. Interestingly, mutations that considerably increase decay acceleration for the classical pathway C3 convertase have been identified that map to residues within our peptide 4 [20]. By making synthetic peptides harboring such mutations we plan on testing their effectiveness in preventing complement-mediated RBC destruction using our assays.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mutagenesis data of SCRs-1-4 have identified several critical residues for decay accelerating activities in the N-terminal domain [16][17][18][19][20]. For example, three positively charged amino acids Arg59, Arg60, and Lys61 at SCR-1/SCR-2 junction, Arg64, Asn65, Thr103, and Thr110 in SCR-2 as well as Gly35 in SCR-1 were found to be important for both decay accelerating activity while Phe82 was required primarily for decay accelerating activity [20]. To date, no structural data for the N-terminal domain of CR1 is available.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Thus, flexibility is likely important for activity in some RCAs, and in particular for the larger ones with multiple binding sites such as factor H and CR1 (and indeed CR2). In this respect, it is probably no coincidence that engineering of RCAs with residues inserted into linkers normally devastates function, that linker residues and intermodular "joints" of RCAs frequently contribute to intermolecular interactions, and that binding sites are often composite involving sub-sites on adjacent modules (Blom et al, 2000;Brodbeck et al, 2000;Jenkins et al, 2005;Krych-Goldberg and Atkinson, 2001;Krych-Goldberg et al, 2005). By binding at the intermodular linker or across multiple modules, ligands will bridge adjacent modules and modulate the overall structure of an RCA.…”
Section: Structure-function Relationships In the Regulators Of Complementioning
confidence: 99%